Marketing Opportunities In The Digital Economy - Bhatia, Swati; Abhishek, Anand (Gyan Management Journal, 2024)
Introduction: The Digital Economy refers to a collection of economic and commercial activities that utilize digital technologies and electronic communications. This type of economy typically includes various sectors and activities such as e-commerce, digital marketing, digital financial services, digital content production, software, computer games, cloud services etc. Focus of Research: This abstract provides a concise overview of the research paper on “Marketing Opportunities in the Digital Economy.” The paper explores the various marketing opportunities that have emerged in the digital economy, driven by advancements in technology and the increasing reliance on digital platforms. It analyzes the strategies and techniques employed by businesses to reach and engage with their target audience in this digital landscape. The abstract also highlights the impact of the digital economy on consumer behavior and the implications for marketers. The findings of this research offer valuable insights for businesses seeking to capitalize on the marketing opportunities presented by the digital economy. Objective: The objective of this research paper is to explore and analyze the various marketing strategies and techniques that have emerged in the digital economy. The paper aims to identify the benefits and challenges of digital marketing, understand the impact of the digital economy on consumer behavior, and provide insights and recommendations for businesses seeking to capitalize on the marketing opportunities in the digital landscape. Learnings: The learnings from this study will contribute to a deeper understanding of examining the digital economy and its impact on businesses and users, as well as evaluating the opportunities for easy and fast access to products and services that can lead to increased efficiency and productivity. It will provide businesses with actionable insights to optimize their digital marketing strategies and enhance their ability to attract and retain customers in the digital age.